Collaboration and crowdsourcing in emergency management. Issue 2 (5th June 2017) - Ernst, Christoph; Mladenow, Andreas; Strauss, Christine
Abstract : Purpose: Emergency managers face coordinative challenges that require a high degree of mobility, flexibility and the ability to interpret heterogeneous, location-dependent information of various sources and quality. Recent information and communication technology-driven developments like crowdsourcing or social networks have opened up new organizational possibilities for emergency managers. To make quick but solid decisions, and improve the coordination of activities performed by crowdsourcees during disaster response, the authors suggest the use of collaborative features from crowdsourcing and inherent availability of resources from social network effects. In this paper, the idea of considering collaboration and crowdsourcing as drivers for flexibility in the design of business processes in the context of emergency management is prepared, the meaning of location-dependent tasks for volunteers is investigated, and the added value of social network effects is substantiated. Design/methodology/approach: This paper is part of an ongoing research project in the field of crowdsourcing. It represents conceptual work that builds on relevant literature. Findings: In terms of emergency management, the paper sheds light on what emergency managers may consider when coordinating activities performed by volunteers and how they may benefit from social network effects. Furthermore, it is shown how they can exploit information using collaboration-based and tournament-like crowdsourcing, how they can benefit from invoking additional resources using weak ties from social networks, and how visualization of information may support decision-making. Practical implications: Exemplary applications to exploit crowdsourcing and social network effects to support improvisation and to respond flexibly in disaster response are given. Originality/value: This paper suggests novel collaborative approaches to support emergency managers in their decision-making. Based on social network analysis, the value of weak ties is elaborated, and based on a taxonomy from crowdsourcing, distinct collaborative alternatives are developed and proposed for application in emergency management.